Migraine headaches among university students using id migraine test as a screening tool - ASİL, TALIP; Oztora, Serdar; Korkmaz, Osman; Dagdeviren, Nezih; Celik, Yahya; Caylan, Ayse; TOP, Mehmet S.; Asil, TALİP (My University, 2011)
Background: Migraine is a significant health problem, especially for the young people, due to its frequency and accompanying morbidity, causing disability and loss of performance. In this study, our aim was to determine the prevalence of migraine headaches among university students in Edirne, a Turkish city.